Childhood Of Great Writers - Mukhlisa Nasimova (Zien Journals, 2022)
The truth of history shows that great people did not easily rise to the podium of greatness by themselves. In this article, we will reflect on the childhood of the great writers of the Turkic peoples
Keywords: literature; autobiographical; psychological image; biography